Role of Gate-16 and Gabarap in Prevention of Caspase-11-Dependent Excess Inflammation and Lethal Endotoxic Shock - Sakaguchi, Naoya; Sasai, Miwa; Bando, Hironori; Lee, Youngae; Pradipta, Ariel; Ma, Ji Su; Yamamoto, Masahiro (Frontiers in Immunology, 2020)
Sepsis is a life-threating multi-organ disease induced by host innate immunity to pathogen-derived endotoxins including lipopolysaccharide (LPS). Direct sensing of LPS by caspase-11 activates inflammasomes and causes lethal sepsis in mice. Inhibition of caspase-11 inflammasomes is important for the prevention of LPS-induced septic shock; however, whether a caspase-11 inflammasome-specific suppressive mechanism exists is unclear. Here we show that deficiency of GABARAP autophagy-related proteins results in over-activation of caspase-11 inflammasomes but not of canonical inflammasomes. Gate-16-/-Gabarap-/- macrophages exhibited elevated guanylate binding protein 2 (GBP2)-dependent caspase-11 activation and inflammatory responses. Deficiency of GABARAPs resulted in formation of GBP2-containing aggregates that promote IL-1β production. High mortality after low dose LPS challenge in Gate-16-/-Gabarap-/- mice primed with poly(I:C) or polymicrobial sepsis was ameliorated by compound GBP2 deficiency. These results reveal a critical function of Gate-16 and Gabarap to suppress GBP2-dependent caspase-11-induced inflammation and septic shock.